2001
DOI: 10.1046/j.1355-557x.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid level on liver and muscle lipid deposition in juvenile haddock, Melanogrammus aeglefinus L.

Abstract: The effects of dietary lipid levels on growth, feed utilization, hepatosomatic index (HSI), liver lipid deposition and tissue fatty acid composition in haddock were investigated. Triplicate tanks of juvenile haddock (6.9 g) were fed graded levels of herring oil to supply 14, 16, 19 and 22% lipid (DM, dry matter) in ®sh meal-based, isonitrogenous diets. Growth and feed conversion ratio of juvenile haddock was not signi®cantly (P < 0.05) affected by increasing the lipid content of the diet. A signi®cant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
62
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 16 publications
(31 reference statements)
11
62
2
Order By: Relevance
“…Given the relatively large size of the fillet (nearly 55% of body mass), muscular mass might also play the important contribution to body fat deposit in the present study for Japanese seabass. This result is different from that observed in other fishes fed high lipid diets (Nanton et al 2001;Lee et al 2002;López et al 2009), but similar to reports in eel (Otwell and Rickards 1981), salmon (Hemre and Sandnes 1999) and cobia (Wang et al 2005). 18:0 5.9 ± 0.3 a 4.7 ± 0.4 b 3.5 ± 0.7 c 4.3 ± 0.2 bc 5.7 ± 1.2 a 6.6 ± 0.9 a 20:0 0.8 ± 0.0 c 0.9 ± 0.1 bc 0.8 ± 0.1 c 1.0 ± 0.3 b 1.1 ± 0.1 b 1.3 ± 0.2 a SFA 24.2 ± 1.1 b 17.8 ± 1.3 c 17.2 ± 0.9 c 18.9 ± 1.8 c 23.9 ± 1.7 b 27.6 ± 3.4 a 16:1n-7 2.5 ± 0.1 c 3.5 ± 0.8 a 2.6 ± 0.5 c 2.9 ± 0.3 b 3.1 ± 0.1 b 3.5 ± 0.5 a 18:1n-9 8.2 ± 0.4 b 6.8 ± 0.6 c 5.1 ± 0.4 d 7.3 ± 0.3 c 8.4 ± 0.8 b 9.2 ± 0.7 a 18:1n-7 3.8 ± 0.6 ab 2.2 ± 0.2 d 2.6 ± 0.…”
Section: Discussioncontrasting
confidence: 79%
“…Given the relatively large size of the fillet (nearly 55% of body mass), muscular mass might also play the important contribution to body fat deposit in the present study for Japanese seabass. This result is different from that observed in other fishes fed high lipid diets (Nanton et al 2001;Lee et al 2002;López et al 2009), but similar to reports in eel (Otwell and Rickards 1981), salmon (Hemre and Sandnes 1999) and cobia (Wang et al 2005). 18:0 5.9 ± 0.3 a 4.7 ± 0.4 b 3.5 ± 0.7 c 4.3 ± 0.2 bc 5.7 ± 1.2 a 6.6 ± 0.9 a 20:0 0.8 ± 0.0 c 0.9 ± 0.1 bc 0.8 ± 0.1 c 1.0 ± 0.3 b 1.1 ± 0.1 b 1.3 ± 0.2 a SFA 24.2 ± 1.1 b 17.8 ± 1.3 c 17.2 ± 0.9 c 18.9 ± 1.8 c 23.9 ± 1.7 b 27.6 ± 3.4 a 16:1n-7 2.5 ± 0.1 c 3.5 ± 0.8 a 2.6 ± 0.5 c 2.9 ± 0.3 b 3.1 ± 0.1 b 3.5 ± 0.5 a 18:1n-9 8.2 ± 0.4 b 6.8 ± 0.6 c 5.1 ± 0.4 d 7.3 ± 0.3 c 8.4 ± 0.8 b 9.2 ± 0.7 a 18:1n-7 3.8 ± 0.6 ab 2.2 ± 0.2 d 2.6 ± 0.…”
Section: Discussioncontrasting
confidence: 79%
“…Haddock liver had significantly high lipid content, which was almost double that of cod and halibut liver. The result for haddock liver lipid level (67.2%) in the present study was in agreement with the previously published data (63.2%−69.0%, Nanton et al, 2001). However, lipid content of cod liver (36.9%) in our study was lower than that (50%−60%) reported by Lie et al (1986), and lipid content of halibut liver (30.7%) in this study was higher than that (7%−19%) reported by Hatlen et al (2005).…”
Section: Discussionsupporting
confidence: 83%
“…In fat fish flesh, triglycerides are the major lipid form, but the structural phospholipids exceeding the high energy triglycerides in lean fish muscle has been observed in previous work (Ackman, 1989;Santos et al, 1993;Nanton et al, 2001). Results of this study were in accordance with those previously reported.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…and shrimp (Pandalus sp.). Prepared dry and moist pellet diets that require less labour are also options, though they are more removed from their natural diet, and due to a relatively high fat content, lead to enlarged livers (Nanton et al, 2001;Lambert and Thorsen, 2003). Fish should be tagged (external or internal) to maintain record of their growth and reproductive history while in captivity.…”
Section: Broodstock Collection and Husbandrymentioning
confidence: 99%